Immigrant Health and Early-Onset Colorectal Cancer Disparities: Results From the Spanish Early-Onset Colorectal Cancer Consortium - José Perea; Marc Martí-Gallostra; Ariadna García-Rodríguez; Rosario Vidal-Tocino; José A. Alcázar; Irene López-Rojo; Sara Encinas García; Elena Hurtado; Luis M. Jiménez; Edurne Álvaro; Ana Burdaspal; Gonzalo Sanz; et al. (JCO Global Oncology)
PURPOSETo better understand immigration disparities among a Spanish Early-Onset Colorectal Cancer (SECOC) subset, according to the country of origin.PATIENTS AND METHODSWe selected 250 consecutive participants from the SECOC consortium. Data on baseline patient and tumor characteristics, family history of colorectal cancer (CRC), and follow-up were collected. The presence of mismatch repair deficiency was also assessed. Special data regarding country of origin, time of stay in Spain in case of other different country, and a 10-year cutoff that specifies the obtaining of Spanish nationality defined the variables of interest for comparison.RESULTSSeventy-five percent of patients with early-onset CRC (EOCRC) (188) were born in Spain, whereas the other 25% were born outside of Spain. The mean time of living in Spain until the EOCRC diagnosis was 16.5 years. Comparatively, most of the analyzed features showed equivalent proportions between cohorts. Only Spanish patients appeared to have more familial cancer component in first degree in general (32.3%; P = .01), compared with non-Spaniards, which showed a predominant sporadic component (56.4%; P < .001). Among immigrants, those patients living in Spain before CRC diagnosis ≤10 years were younger at diagnosis (39.1 v 42.5), more frequently male (77.8 v 47.7), were in more advanced stages (88.8% diagnosed at stage III and IV [P = .01]), and had a worse prognosis regarding recurrence rates (29.4% v 6.3%).CONCLUSIONAlthough there were few differences between Spanish and non-Spanish EOCRC, the most remarkable difference was that linked with the situation of those immigrants who have recently arrived in Spain, in relation to their lower health coverage, which could be associated with the delay in the diagnosis and their subsequent worse prognosis.